The Cloisters : a novel - Hays, Katy, 1982- (Atria Books, 2022)
"The Secret History meets Ninth House in this sinister, atmospheric novel following a circle of researchers as they uncover a mysterious deck of tarot cards and shocking secrets in New York's famed Met Cloisters. When Ann Stilwell arrives in New York City, she expects to spend her summer working as a curatorial associate at the Metropolitan Museum of Art. Instead she finds herself assigned to The Cloisters, a gothic museum and garden renowned for its medieval art collection and its group of enigmatic researchers studying the history of divination. Desperate to escape her painful past, Ann is happy to indulge the researchers' more outlandish theories about the history of fortune telling. But what begins as academic curiosity quickly turns into obsession when Ann discovers a hidden 15th-century deck of tarot cards that might hold the key to predicting the future. As the dangerous game of power, seduction, and ambition at The Cloisters turns deadly, Ann becomes locked in a race for answers as the line between the arcane and the modern blurs. A haunting and magical blend of genres, The Cloisters is a gripping debut that will keep you on the edge of your seat"--